The Language of Water: Interspecies Dialogue in a Context of Crisis - Barcia Sánchez, Fernando (2026)
In the Tsotsil communities of the Los Altos region of Chiapas (Mexico), water sources, springs, and wells set in motion a whole series of relationships between humans and non-humans (spirits, owners, etc.) intertwined in a common agency that makes it possible for crops to grow successfully and disease to stay away from communities. In short, it makes life good. For approximately five years, a series of crises (the COVID-19 pandemic, climate change, drug trafficking in the region, and the proliferation of garbage dumps) have altered the conditions necessary to maintain these relationships, resulting in silence on the part of non-humans. In this text, we will analyze how water sources bring about dialogue between humans and non-humans, how this dialogue is affected by the crises shaking the region, and finally, how Tsotsil communities are tackling the task of rebuilding the dialogue between water, humans, and non-humans.